2001
DOI: 10.1111/j.1744-6171.2001.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Restraint-Reduction Program for Child/ Adolescent Inpatient Treatment

Abstract: By combining what is known about child/adolescent restraint use with restraint-reduction research in the adult field, several options for restraint reduction can be derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…Also discussed is how these measures are influenced by the overall unit functioning [5,18,20], changes to policy and procedures [5,19,21] and legal changes [2,22]. Concerns about seclusion and restraint use arise from clinicians, administrative staff and the wider community and success in decreasing seclusion and restraint rates is reported [5,17,21,23,24].…”
Section: Patterns Of Usementioning
confidence: 99%
“…Also discussed is how these measures are influenced by the overall unit functioning [5,18,20], changes to policy and procedures [5,19,21] and legal changes [2,22]. Concerns about seclusion and restraint use arise from clinicians, administrative staff and the wider community and success in decreasing seclusion and restraint rates is reported [5,17,21,23,24].…”
Section: Patterns Of Usementioning
confidence: 99%
“…In other studies, nurses who saw restraint as unacceptable could find it difficult to choose between causing harm and promoting health (Ives & Melrose, 2010; Lloyd, Urquhart, Heard, & Kroese, 2008; McGrath & Huff, 2003). Delaney (2001) performed an ethical analysis of nurses’ perspectives on the harm of restraint versus the benefit in psychiatric settings and concluded that holding a child was perceived as “reasonable harm” compared with the benefit of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As Wynaden et al (2001) point out, understanding staff perceptions, patient responses, and issues that led up to restraint could facilitate new ideas about aggression management. It is argued here that the United States should not embrace training formulas to the extent that the contextual factors of aggression management are ignored and opportunities for developing new management techniques missed (Delaney 2001).…”
Section: Resultsmentioning
confidence: 99%